2015
DOI: 10.18632/oncotarget.4351
|View full text |Cite
|
Sign up to set email alerts
|

High copy number variation of cancer-related microRNA genes and frequent amplification ofDICER1andDROSHAin lung cancer

Abstract: A growing body of evidence indicates that miRNAs may be a class of genetic elements that can either drive or suppress oncogenesis. In this study we analyzed the somatic copy number variation of 14 miRNA genes frequently found to be either over- or underexpressed in lung cancer, as well as two miRNA biogenesis genes, DICER1 and DROSHA, in non-small-cell lung cancer (NSCLC). Our analysis showed that most analyzed miRNA genes undergo substantial copy number alteration in lung cancer. The most frequently amplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 94 publications
(100 reference statements)
1
62
0
Order By: Relevance
“…Karyotype copy number alterations were previously associated with deregulated miRNA expression in some cancers and miRNA coding regions show high frequency of copy number variations in ovarian, breast, melanoma and lung cancer [41,42]. Interestingly, some studies report no correlation between the copy number status and miRNA expression in haematopoetic cancer and acute myeloid leukemia [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Karyotype copy number alterations were previously associated with deregulated miRNA expression in some cancers and miRNA coding regions show high frequency of copy number variations in ovarian, breast, melanoma and lung cancer [41,42]. Interestingly, some studies report no correlation between the copy number status and miRNA expression in haematopoetic cancer and acute myeloid leukemia [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Another pan‐cancer study indicated that the genomic loci harbouring miRNAs genes exhibited high proportion of somatic copy number alterations accounting for about 37.1% in ovarian cancer, 72.8% in breast cancer and 85.9% in melanomas (Zhang et al ., 2006). miRNA genes were also demonstrated to undergo substantial SCNAs in lung cancer, with miR‐30d, miR‐21, miR‐17 and miR‐155 being the most amplified ones (Czubak et al ., 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Czubak et al [45] showed several miRNA genes (miR-30d, miR-21, miR-17 and miR-155), as well as two miRNA biogenesis genes, DICER1 and DROSHA, to be frequently amplified in tumour tissue specimens from 254 NSCLC patients. Moreover, the copy number variation of DICER1 and DROSHA correlated well with their expression cell-free miRNA in plasma serial blood collecƟon during treatment Fig.…”
Section: Mirna Biogenesis and Functionmentioning
confidence: 99%